Gastrointestinal Stromal Tumours: Consensus Statement on Diagnosis and Treatment. (2006) - Blackstein, Martin E; Blay, Jean-Yves; Corless, Christopher; Driman, David K; Riddell, Robert; Soulières, Denis; Swallow, Carol J; Verma, Shailendra; on behalf of the Canadian Advisory Committee on GIST,
Abstract : In the multidisciplinary management of gastrointestinal stromal tumours (GISTs), there is a need to coordinate the efforts of pathology, radiology, surgery and oncology. Surgery is the mainstay for resectable nonmetastatic GISTs, but virtually all GISTs are associated with a risk of metastasis. Imatinib 400 mg/day with or without surgery is the recommended first-line treatment for recurrent or metastatic GIST; a higher dose may be considered in patients who progress, develop secondary resistance or present with specific genotypic characteristics. Adjuvant or neoadjuvant imatinib is not advised for resectable non-metastatic GISTs. Neoadjuvant imatinib may be considered when surgery would result in significant morbidity or loss of organ function. Follow-up computed tomography imaging is recommended every three to six months for at least five years. Patients with metastatic disease should be continued on imatinib due to the high risk of recurrence on discontinuation of therapy. Treatment should be continued until there is progression or intolerable adverse effects. If dose escalation with imatinib fails, a clinical trial with novel agents alone or in combination may be considered. The present recommendations were developed at a surgical subcommittee meeting and a subsequent full Advisory Committee meeting held in Toronto, Ontario, in April 2005, under the sponsorship of Novartis Pharmaceuticals Canada Inc.